The impact of macroeconomic and monetary policy shocks on credit risk in the euro area corporate sector - Marco Lo Duca; Diego Moccero; Fabio Parlapiano (European Central Bank (ECB), 2024)
We analyse the impact of macroeconomic and monetary policy shocks on corporate credit risk as measured by firms' probabilities of default (PDs) for the four largest euro area countries. We estimate the impact of shocks on one-year PDs using local projections (LP). For the period 2014-19, we find that aggregate shocks significantly affect the dynamics of credit risk. An adverse supply shock leads to a deterioration of firms' riskiness 10 per cent above the average PD. Contractionary monetary policy shocks exert similar, but delayed effects. Firms' responses to shocks vary depending on their characteristics and degree of financial constraints. Smaller firms are affected to a larger degree. Firms' outstanding indebtedness and debt repayment capacity are an important transmission channel for aggregate shocks, but the accumulation of cash reserves helps building resilience.
Keywords: C23; C55; E43; E52; G33; 330; Corporate credit risk; probabilities of default; structural demand and supply shocks; monetary policy shocks; local projections